On slowdown variance as a measure of fairness - Vincent J. Maccio; Jenell Hogg; Douglas G. Down (Operations Research Perspectives, 2018)
When considering fairness one must ask two fundamental questions. Firstly, what does it mean to be fair? And secondly, how does one measure that fairness? Different authors have offered different notions and metrics to address these questions. We provide arguments identifying where past metrics fall short, discuss how the underlying motivations differ, and offer our own metric to address these issues. That is, we propose using a system's slowdown variance (SDV) as a measure for its fairness. Advantages of SDV are demonstrated via a suite of simulation experiments which compare a range of established policies under a range of service time distributions. These advantages include a decoupling of fairness from performance, an intuitive distinction between last come first serve and processor sharing, as well as recognition of starvation within shortest remaining processing time.
Keywords: 330; Gerechtigkeit; Messung; Statistische Bestandsanalyse; Operations Research